Denaturation of DNA Double-Helix Characterized by Thermal Conductance - 杨明明 钟伟荣 (Chinese physics letters, 2014)
We deal with the thermal conductance and the denaturation of a three-dimensional DNA double helix based on the Peyrard-Bishop-Dauxois model by using non-equilibrium molecular dynamics simulations. It is reported that the thermal conductance of DNA has a substantial decrease near the denaturation where the DNA double helix separates into two single chains. We explain this phenomenon through the phonon spectra at different temperatures. It is suggested that the denaturation of DNA can also be characterized by the change of the thermal conductance.